PENGEMBANGAN PETANI ANGGREK DESA PLOSOREJO MATESIH KARANGANYAR - Sri Hartati; LINAYANTI LINAYANTI (JURNAL ILMIAH AGRINECA, 2015)
The purpose of the introduction of species of orchids nature, germplasm conservation of natural orchids that species is not extinct, increasing the genetic diversity of natural orchids through crossbreeding. Indonesia has a rich diversity of germplasm of wild orchids that have economic value and not all identified. To add to the natural genetic diversity as a source of genetic Orchids can be reached by crossing / hybridization. Hybridization and selection program geared to improve the genetic quality and economic value of nature orchid market. The types of natural orchids (orchid forest) have not been developed in the area of the District Plosorejo Kedongdowo Matesih. Given the types of wild orchids have a fairly high biodiversity and endangered species that need to be preserved. Efforts to improve the genetic quality of orchids have constraints   on   the   crossing   and   propagation   techniques   seeds   from   crosses. Service activities have been undertaken to increase natural orchid plant development by providing counseling introduction to the types of natural orchids (orchid jungle) with their morphological characters and techniques on how to cross.